Measuring Urban Sprawl - how Can we Deal with It? - Amnon Frenkel; Maya Ashkenazi (European Regional Science Association (ERSA), 2005)
Measuring urban sprawl is a controversial topic among scholars who investigate the urban landscape. In fact, most researchers agree that sprawl is a complex phenomenon, and moving from "sprawl” to "compact” form is more likely to be a direction on a continuum rather than a fixed and measurable category. This study attempts to measure sprawl in Israel from a landscape perspective. The measures and indices used in the study derive from various research disciplines, such as urban research, ecological research, and fractal geometry. Five main groups of indices that quantify the urban landscape were included in the research: density, shape/fractals, leapfrog, mean patch size, and land-use composition. The examination was based on an urban land-use survey that was performed in 78 urban settlements over the course of 15 yeas. Thirteen measures of sprawl were calculated at each settlement and then weighted into one integrated sprawl index through factor analysis. The calculations were performed for the beginning and the end of the period investigated, thus enabling a description of sprawl rates and their dynamics during a time period of two decades. The results show that urban sprawl is a multidimensional phenomenon that is better quantified by various measures; thus, it cannot be measured by only one or two popular measures, such as density or growth rates, as often is done in many urban studies. In addition, the results indicate that most urban settlements in Israel showed less sprawling and became more compact during the past two decades: density and mean patch-size measures became higher; shape, fractal, and leapfrog measures became lower; and land-use composition did not dramatically change during the period investigated. Furthermore, some measures were found to be more dominant and effective and others less effective on a municipal scale.
Keywords: 330